Design and Analysis of a 3-DOF Rigid Motion Stage - Yogesh singh; Saurabh, Sunny Kumar (Journal of Advanced Research in Mechanical Engineering and Technology, 2026)
In this paper, a rigid motion stage having three degrees of freedom (DOF) translation along the X and Y axes and rotation about the Z axis is investigated. The configuration of the motion stage is 2PPR (Prismatic-Prismatic-Revolute) 1PRR (Prismatic- Revolute-Revolute). In this work, workspace of motion was determined using finite element analysis (FEA) carried out in ANSYS Workbench. The workspace of the proposed motion stage was calculated as 127.59 mm in the X direction and 46.18 mm in the Y direction. The first six mode shapes and their respective frequencies were obtained through dynamic analysis, which is another aspect of this study. The first natural frequency of 156.43 Hz, which is relatively high for a wide-range mechanism, was observed in order to ensure operational stability. The findings demonstrate the design’s structural stability and potential applications in precision manufacturing, robotics, optics, and micromanipulation. This approach is innovative because it provides a comprehensive view of the motion stage’s performance by integrating workspace analysis with dynamic behaviour assessment.